2017
DOI: 10.1002/2017jg003963
|View full text |Cite
|
Sign up to set email alerts
|

In situ 15N labeling experiment reveals different long‐term responses to ammonium and nitrate inputs in N‐saturated subtropical forest

Abstract: Chronically elevated deposition of reactive nitrogen (N), as ammonium (NH 4 +) and nitrate (NO 3 À), in subtropical forests with monsoonal climate has caused widespread N leaching in southern China. So far, little is known about the effect of further increases in N input and changes in the relative proportion of NH 4 + and NO 3 À on turnover rate and fate of atmogenic N. Here we report a 15 N tracer experiment in Tieshanping (TSP) forest, SW China, conducted as part of a long-term N fertilization experiment, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 60 publications
(111 reference statements)
2
28
3
Order By: Relevance
“…The importance of NO 3 − leaching is supported by the significant recovery of 15 N in the deeper AB horizon (Figure S5, supporting information) . Significant loss of labeled NO 3 − from the soil was also observed in a recent study at the same site . In addition to leaching, the atom% 15 N in NO 3 − also declined due to dilution by NO 3 − produced from nitrification of non‐labeled NH 4 + , which showed stable atom% 15 N close to natural abundance throughout the experiment (Figures B and D).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The importance of NO 3 − leaching is supported by the significant recovery of 15 N in the deeper AB horizon (Figure S5, supporting information) . Significant loss of labeled NO 3 − from the soil was also observed in a recent study at the same site . In addition to leaching, the atom% 15 N in NO 3 − also declined due to dilution by NO 3 − produced from nitrification of non‐labeled NH 4 + , which showed stable atom% 15 N close to natural abundance throughout the experiment (Figures B and D).…”
Section: Resultssupporting
confidence: 68%
“…19 Significant loss of labeled NO 3 − from the soil was also observed in a recent study at the same site. 34 In addition to leaching, the atom% 15 production, 19 we show here that nitrification is the main source of NO.…”
Section: No Emission Rates Measurements and Modelingmentioning
confidence: 64%
“…It should be noted that nitrate leaching did not cease in this study, indicating that N saturation should still exist under current N deposition. In actuality, previous studies showed clear N saturation at TSP, with nearly all added N leached by soil water (Huang et al, ; Liu, Yu, et al, ). It is believed that N leaching only begins to increase significantly after the soil reaches N‐saturation (Aber & Magill ; Fang et al, ; Huang et al, ; Larssen et al, ).…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, in addition to acidification, N saturation caused by increased N deposition may result in the eutrophication of soil and water, the emission of N 2 O (a potent greenhouse gas that is increasingly important in the destruction of stratospheric ozone; Fang et al, ; Li et al, ; Ravishankara et al, ), and reduced biodiversity and forest growth (Aber et al, ; Aber et al, ; Kreutzer et al, ; Lu et al, ; Pardo et al, ). Therefore, an “explosion” in N effect studies has occurred in Asia, especially in China, during the past few decades, both in forests and grasslands (Bai et al, ; Chen et al, ; Guo et al, ; Huang et al, ; Li et al, ; Liu, Yu, et al, ; Liu, Zhang, et al, ; Lu et al, ; Wei et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation